Evaluation of Serum Biochemistry of Uda Rams Managed Under Different Housing Conditions and Season in Semi-arid region of Nigeria - Aljameel, K. M; Mikailu, M. M.; Musa, B. M.; Ibrahim, S.; Imoagene, J. O. (European Journal of Applied Sciences, 2025)
A study was conducted at the Usmanu Danfodiyo University, Sokoto, Livestock Teaching and Research Farm to evaluate the effects of housing type and season on the performance and some physiological parameters of Uda rams. A total of sixty (60) yearling Uda rams were used in the study with twenty (20) rams in each season. Factorial completely randomised design (3x5) was used in this experiment with animals (4) representing replicates while housing types (5) and season (3) representing the factors (treatments). Four animals were allotted to each housing types with each animal serving as replicate, the housing types were half wall with zinc roofing (HZ), half wall with thatch roofing (HT), full wall with zinc roofing (FZ), full wall with thatch roofing (FT) and finally natural without wall and roofing (N). At the end of each season blood was collected for analysis. The data generated were analysed. In the hot season, there was significant (P<0.05) variation in all parameters (albumin, globulin, total protein, HDL, LDL, triglycerides, creatinine, cholesterol, urea and glucose). In rainy season animals placed in N have significantly (P<0.05) higher values of total protein, globulin and urea, while those in HZ had higher (P<0.05) values of urea, total protein and globulin. In cold season, there was no significant (P>0.05) variation in of albumin, HDL, LDL, triglycerides and cholesterol. There was lower (P<0.05) globulin and creatinine for animals placed in FZ and HT respectively compared to the other housing types.